Implementation of Cooperative Script Model in Teaching Islamic Education in Elementary School - Alias, Muhamad Firdaus Bin; Rahman, Rini; Mahaiyadin, Mohd Hapiz Bin; Rivauzi, Ahmad; Subri, Irwan Bin Mohd; Wirdati, Wirdati; Sulaiman, Sulaiman (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2024)
This research aims to incorporate the Cooperative Script Learning Model into Islamic Religious Education subjects. In addition, this research also proposes a comprehensive conceptual framework for teaching students to overcome problems related to student focus. This initiative aims to involve students in the learning process, as implemented by elementary school teachers. This research uses a qualitative thematic methodology to investigate the phenomenon under study. Data was collected through structured interviews with 26 elementary school participants. Informant data using snowball sampling technique. The findings of this research indicate that there are several variables that impact student learning outcomes, in addition to the influence of student skills and the learning approach chosen by the instructor. The results of this research can be basic data for further research that explores the Cooperative Script Learning Model in Schools in various contexts and aspects.